Research on Territorial Spatial Use Regulation, Land Element Allocation, and Regional Fiscal Transfer Payments: An Empirical Study of the Yangtze River Economic Belt - Wanmin Zhao; Yijia Gao; Aihui Ma (Land)
The regulation of land use within territorial spaces has, to some extent, inhibited the free flow of land resources, giving rise to the dilemma of substantial losses and profits within and outside regulated areas. Investigating how to allocate “windfall profits” to compensate the regions that suffer windfall losses is of great importance for addressing regional development imbalances. This study, based on the perspective of restricted land development rights, employed an improved Cobb–Douglas (C-D) production function to analyze the differences in land input contributions between the agricultural and non-agricultural sectors. It quantified the extent of restricted land development rights, assessed their value using the opportunity cost method, and applied an economic adjustment coefficient to revise the regional fiscal transfer amounts. The results indicate the following: (1) The contribution of land factors to economic output is more significant in the non-agricultural sector than in the agricultural sector. (2) There are substantial differences in the quantities of restricted land development rights and their unit values across provinces and cities. Anhui Province has the largest restricted area, at approximately 71,945.52 hectares, while Guizhou Province has the smallest, at about 6452.62 hectares. Shanghai has the highest unit value, at around CNY 13.77 million per hectare, whereas Yunnan Province has the lowest, at approximately CNY 1.4748 million per hectare. (3) The total fiscal transfer amount for the provinces in the Yangtze River Economic Belt is about CNY 23.4 billion. Anhui Province receives the most compensation, at approximately CNY 8.5 billion, while Jiangsu Province has the highest expenditure, at about CNY 19.8 billion. Currently, the state should establish a comprehensive regional fiscal transfer compensation mechanism that takes into account the fiscal payment capacities of “windfall profit regions” and the incentive effects on “windfall loss regions” when determining fiscal transfer amounts. This approach aims to alleviate potential fiscal payment resistance in “windfall profit regions” and enhance proactive protection efforts in “windfall loss regions”, thereby achieving the coordinated development of economic growth, ecological improvement, and food security.